Analisis Pengaruh Fee Audit, Audit Tenure, Rotasi Audit dan Reputasi KAP terhadap Kualitas Audit: Studi pada Perusahaam Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Violetta Rifqi Agastya; Vania Belva Abidah Ardelia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study was to determine the effect of fee audit, audit tenure, audit rotation, and KAP reputation on audit quality. The research population is all manufacturing companies listed on the Indonesia Stock Exchange. The sample consisted of 22 manufacturing companies that met the predetermined criteria to be sampled throughout the study period. The sampling methodology used in this study is purposive sampling. The methodology used for data analysis in this study is logistic regression analysis. Secondary data in the form of the company's annual financial statements obtained from the official website of the Indonesia Stock Exchange (IDX) and each sample company were used for this study. The data collection process includes documenting information and analysis using the SPSS 25 application program. The research results show that audit fees have a positive but not significant effect on audit quality, audit tenure has a statistically insignificant negative impact on audit quality, audit rotation has a statistically significant positive impact on audit quality, and KAP reputation has a statistically significant positive impact on audit quality, according to the research findings.